Evolving Knowledge on Primary and Secondary Prevention of Venous Thromboembolism in Carriers of Hereditary Thrombophilia: A Narrative Review - Campello, Elena; Prandoni, Paolo (Seminars in Thrombosis and Hemostasis, 2022)
The association between heritability of venous thromboembolism (VTE) and thrombophilia was first reported clinically in 1956, later followed by the first description of a congenital cause of hypercoagulability—antithrombin deficiency—in 1965. Since then, our knowledge of hereditary causes of hypercoagulability, which may predispose carriers to VTE has improved greatly. Novel genetic defects responsible for severe thrombophilia have been recently identified and we have learned that a wide range of interactions between thrombophilia and other genetic and acquired risk factors are important determinants of the overall individual risk of developing VTE. Furthermore, therapeutic strategies in thrombophilic patients have benefited significantly from the introduction of direct oral anticoagulants. The present review is an overview of the current knowledge on the mechanisms underlying inherited thrombophilia, with a particular focus on the latest achievements in anticoagulation protocols and prevention strategies for thrombosis in carriers of this prothrombotic condition.
Keywords: thrombophilia; hypercoagulability; venous thrombosis; heparin; direct oral anticoagulants